Structural Biology of the FGF7 Subfamily - Zinkle, Allen; Mohammadi, Moosa (Frontiers in Genetics, 2019)
Mammalian fibroblast growth factor (FGF) signaling is intricately regulated via selective binding interactions between 18 FGF ligands and four FGF receptors (FGFR1-4), three of which (FGFR1-3) are expressed as either epithelial (“b”) or mesenchymal (“c”) splice isoforms. The FGF7 subfamily, consisting of FGF3, FGF7, FGF10, and FGF22, is unique among FGFs in that its members are secreted exclusively by the mesenchyme, and specifically activate the “b” isoforms of FGFR1 (FGFR1b) and FGFR2 (FGFR2b) present in the overlying epithelium. This unidirectional mesenchyme-to-epithelium signaling contributes to the development of essentially all organs, glands, and limbs. Structural analysis has shown that members of the FGF7 subfamily achieve their restricted specificity for FGFR1b/FGFR2b by engaging in specific contacts with two alternatively spliced loop regions in the immunoglobulin-like domain 3 (D3) of these receptors. Weak basal receptor-binding affinity further constrains the FGF7 subfamily’s specificity for FGFR1b/2b. In this review, we elaborate on the structural determinants of FGF7 subfamily receptor-binding specificity, and discuss how affinity differences among the four members for the heparan sulfate (HS) co-receptor contribute to their disparate biological activities.